Biodiesel production from date seed oil (Phoenix dactylifera L.) via egg shell derived heterogeneous catalyst - Farooq, M. (Institution of Chemical Engineers, 2018)
This work explains the preparation of an efficient catalyst from waste chicken egg shells for exploring environment-friendly and cost-effective biodiesel production process for socio-economic growth. XRD, BET, TGA, and TPD-CO2 analysis were employed to evaluate the physicochemical properties of the prepared catalysts. The catalytic performance of the synthesized catalysts was tested in biodiesel production via transesterification from date seed oil under different reaction conditions. It was found that catalyst prepared at 900 Â°C exhibited excellent transesterification activity and provided maximum yield of fatty acid methyl esters up to 93.5 under optimal reaction conditions, i.e. reaction time of 1.5 h, methanolâoil molar ratio of 12:1, and catalyst amount of 5 wt.. In addition, the catalyst exhibited substantial stability and reusability during biodiesel conversion. Â© 2018 Institution of Chemical Engineers